Effects of milling time on the microstructure and properties of FeCoNiMnAl magnetic high-entropy alloys. (March 2023) - Luo, Wenqi; Zou, Qin; Li, Yanguo; Ye, Xihui; Dai, Lifeng; Zhu, Wenshuai; Yang, Xiaowei; Luo, Yongan
Abstract: FeCoNiMnAl magnetic high-entropy alloys (HEAs) were prepared by mechanical alloying and spark plasma sintering (SPS). The effects of milling time on the microstructure evolution, hardness, compressive strength, and magnetic properties of FeCoNiMnAl HEAs including powders and sintered bodies were investigated. After 30 h of milling, the HEA powders formed a solid solution with predominately face-centered cubic (FCC) phase structure and a small amount of body-centered cubic (BCC) phase. With a further increase in milling time, the BCC phase was transformed into the FCC phase. In the course of the BCC-to-FCC transformation, the hardness and compressive strength noticeably increased, while the magnetic properties of the alloys slightly decreased. Moreover, the decrease in lattice parameter of the FCC phase was shown to be an important factor enhancing the magnetic properties of HEAs. Besides, the high saturation magnetization of 84.7 emug was achieved in HEA-4. The maximum hardness and compressive strength of the samples were found to be 577 HV and 2099 MPa, respectively. Graphical Abstract: ga1